Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/resp.14363
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer in patients with idiopathic pulmonary fibrosis: A retrospective multicentre study in Europe

Abstract: Background and Objective There remains a paucity of large databases for patients with idiopathic pulmonary fibrosis (IPF) and lung cancer. We aimed to create a European registry. Methods This was a multicentre, retrospective study across seven European countries between 1 January 2010 and 18 May 2021. Results We identified 324 patients with lung cancer among 3178 patients with IPF (prevalence = 10.2%). By the end of the 10 year‐period following IPF diagnosis, 26.6% of alive patients with IPF had been diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…Finally, it is also interesting that another mediator of cancer, SHP2, is a potential therapeutic target for pulmonary fibrosis [ 35 , 36 , 37 ]. Focusing on commonalities between cancer and pulmonary fibrosis might lead to novel anti-fibrotic compounds, similarly with the process of nintedanib repositioning [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is also interesting that another mediator of cancer, SHP2, is a potential therapeutic target for pulmonary fibrosis [ 35 , 36 , 37 ]. Focusing on commonalities between cancer and pulmonary fibrosis might lead to novel anti-fibrotic compounds, similarly with the process of nintedanib repositioning [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the incidence of lung cancer in IPF patients increases over time, being 3.3% 1 year after diagnosis and racing to 54.7% after 10 years. In a previous study, we demonstrated that the expression of B4GALT1 was linked to tumor development and progression [ 5 , 8 ]. Lung cancer was prevalent and exerted a dramatic survival impact on patients with IPF [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated that the expression of B4GALT1 was linked to tumor development and progression [ 5 , 8 ]. Lung cancer was prevalent and exerted a dramatic survival impact on patients with IPF [ 8 ]. However, the expression of B4GALT1 in IPF tissue and cell lines, as well as in UIP/IPF associated with lung cancer, was never tested before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have read with interest the article by Karampitsakos et al 1 The authors established a large, multinational cohort of idiopathic pulmonary fibrosis (IPF), and compared survival, the primary outcome, by specific subgroups. In this study, the authors suggested that comorbid lung cancer increased all-cause mortality in IPF patients, while the administration of antifibrotics and surgery when technically resectable decreased all-cause mortality in IPF patients with comorbid lung cancer.…”
Section: To the Editorsmentioning
confidence: 99%